THE EFFECTS OF STUDENTS’ VOCABULARY AND GRAMMAR MASTERY TOWARDS ENGLISH RECOUNT WRITING SKILL IN THE SECOND GRADE OF PRIVATE JUNIOUR HIGH SCHOOL IN TANGERANG - Erni Susianti Nainggolan (Universitas Pamulang, 2019)
AbstractThe purpose of this research is to obtain empirical data about the effects of students’ vocabulary and grammar mastery towards English recount writing skill. There are the effects of students’ vocabulary (X1) and grammar mastery(X2) towards students’ English recount writing skill (Y). That is proved by the result Fobservedis 679.878 with significance probability level Sig 0.000. The probability value is (0.000) less than 0.05. It means the regression model could be used to predict the students’ skill in writing. The result of data analysis, the multiple regression in which the multiple correlation coefficient, is ( R ) is 0.987 or (ryx1x2 = 0.987). It means it gives strong effects among them. The simultaneous contribution of perception on the teacher’s competence and grammar mastery towards students’ writing skill is R2 x 100% or 0.987 2 x 100% = 97.4 % and the rest 2.6 % determined by the other factors. In conclusion H0 is rejected and H1 is accepted significantly. There is no effect of students’ vocabulary (X1) toward students’ English recount writing skill (Y). It can be proved tobserved 1.574 meanwhile ttable = 1.69. Because of the score of Sig> 0.05 (0.124>0.05) and tobserved<ttable(1.57 <1.69). The score of Sig = 0.124 means H0 is accepted it means that there is no significant effect of student’s vocabulary toward students’ English recount writing skill. From the test of correlation and regression it can be concluded that there is no effect of students’ vocabulary towards students’ English recount writing skill. There is an effect between grammar mastery (X2) toward students’ writing skill (Y). It can be proved by tobserved 14.718 meanwhile ttable = 1.69. Because of the score of Sig< 0.05 (0.000<0.05) and tobserved>ttable(14.718 > 1.69) determination of regression significance criteria is the score of Sig = 0.000 means H0 is rejected. It means that there is a significant effect of grammar mastery towards students’ English recount writing skill.Keywords: Recount Text, Grammar Mastery, Regression Significance, Vocabulary, Writing Skill,